The Impact Mechanism of Value Co-Creation on Enterprise Performance - Jia, Suying; Adilbish, Gelegjamts; Sharkhuu, Batzusem (International Journal of Global Economics and Management, 2025)
In the contemporary business landscape, which is characterized by the integration of digital technologies with numerous industries, the concept of value co-creation is becoming an increasingly important and creative competitive strategy. Scholars have highlighted the absence of robust arguments and theoretical guidance for organizations seeking to implement value co-creation practices with consumers. This thesis employs the theory of value co-creation as a foundational framework and a mixed-methods approach, utilizing structural equation modelling (SEM), to investigate the mechanism through which value co-creation affects enterprise performance. The findings of the research demonstrate that business model innovation acts as a mediating factor between value co-creation and enterprise performance, while internal process management exerts a moderating influence between the two. It is recommended that the findings of this research be employed to develop efficacious strategies for the implementation of value co-creation in enterprise practice management, with the objective of enhancing enterprise performance.